2014
DOI: 10.1111/jpn.12256
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between changes in intestinal microbiota composition and performance parameters in broiler chickens

Abstract: Growing male Cobb broiler chickens were fed on diets supplemented with additives reported as able to influence intestinal microbiota composition. The diets used were a balanced commercial diet (no additive), inulin (20 g/kg), fructose caramel (FC, 20 g/kg) and the garlic derivative PTS-O (propyl propane thiosulfonate, 45 and 90 mg/kg diet). The composition of the intestinal microbiota was analysed by qPCR at different points of the intestinal tract, and a number of nutritional parameters were also determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 23 publications
3
37
2
Order By: Relevance
“…For example, Clostridium cluster IV counts include butyrate‐producer strains like Faecalibacterium prausnitzii (Rinttilä & Apajalahti, ), which is an energy source for colonocytes, and also affect host metabolism, especially through insulin and leptin pathways (van de Wouw et al, ). The lack of correlation between performance and Clostridium cluster XIV in our study is in discordance with previous reports (Chambers et al, ; Rubio et al, ). The high genetic diversity within the Clostridium cluster XIV group could explain these differences, and should be further investigated.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…For example, Clostridium cluster IV counts include butyrate‐producer strains like Faecalibacterium prausnitzii (Rinttilä & Apajalahti, ), which is an energy source for colonocytes, and also affect host metabolism, especially through insulin and leptin pathways (van de Wouw et al, ). The lack of correlation between performance and Clostridium cluster XIV in our study is in discordance with previous reports (Chambers et al, ; Rubio et al, ). The high genetic diversity within the Clostridium cluster XIV group could explain these differences, and should be further investigated.…”
Section: Discussioncontrasting
confidence: 78%
“…An interesting result was that Enterobacteriaceae family copy numbers increased in the energetic restricted broilers. It is known that a high proliferation of enterobacteria is associated with mucosa damage, which impair nutrient absorption in the jejunum and ileum (Rubio et al, ), and with metabolic deteriorations in host via bacterial endotoxins (Fei & Zhao, ). Similar patterns of microbiota changes were found in mice after weaning (Lutgendorff et al, ), and in caecum of broilers feeding a high fibre diet (Walugembe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PTS-O was able to significantly increase and modulate the composition of bifidobacteria in growing broilers; which are considered as excellent candidates of probiotics in broilers [108]. Another study involving PTS-O supplementation indicated negative correlations between relative abundances of Escherichia-Shigella or enterobacteria (crop, ileum and caeca) and growth performance as well as fat digestibility in PTS-O fed broilers [109]. When garlic extract (0.04 or 0.06 g/kg feed) was gavaged to broilers reduced number of E. coli and Staphylococcus aureus in the ileo-caecal digesta and improved nutrient digestibility were observed [110].…”
Section: Effects On Intestinal Microbiota and Morphologymentioning
confidence: 99%
“…It was shown that skatole production was decreased in the large intestine of pigs by the feed added NDC (Jensen & Hansen, 2006;Lösel, Lacorn, Büttner, & Claus, 2006;Øverland, Kjos, Fauske, Teige, & Sorum, 2011). Non-digestible carbohydrates reaching the large intestine are available for microbial fermentation and affect the microbial community (Knudsen, Hedemann, & Laerke, 2012;Rubio et al, 2015). It has been reported that the prebiotic effects of inulin-derived fructans on humans (Salazar et al, 2015) and broilers (Aead, Ghareeb, & Böhm, 2011;Kareem, Loh, Foo, Akit, & Samsudin, 2016;Pruszynska-Oszmalek et al, 2015).…”
mentioning
confidence: 99%